The Effect of Stretching Exercises on Reducing Joint Pain Levels Among Elderly Prolanis Participants at The Purwoyoso Community Health Center - Aprilia Ardi Kusumadewi; Heny Prasetyorini (Hippocratica : Journal of Modern Medicine and Healthcare Practice, 2026)
Joint pain represents one of the most common health problems affecting older adults and frequently contributes to functional limitation, reduced mobility, and decreased quality of life. This study aimed to evaluate the effect of stretching exercises on reducing joint pain levels among elderly participants enrolled in the Chronic Disease Management Program at the Purwoyoso Community Health Center, Semarang, Indonesia. The study employed a quantitative quasi experimental design using a one group pretest and posttest approach. A total of 35 elderly participants were selected through purposive sampling based on predefined eligibility criteria. Joint pain intensity was assessed using the Numeric Rating Scale before and after a structured stretching exercise intervention. Descriptive statistics were used to describe pain distribution, while the Wilcoxon Signed Rank Test was applied to determine intervention effectiveness. Findings showed that all participants initially experienced moderate pain, whereas postintervention assessment indicated a substantial increase in mild pain classification and a corresponding reduction in moderate pain levels. Statistical analysis demonstrated a significant decrease in pain intensity with a p value of 0.000. Structured stretching exercises were effective in reducing joint pain among elderly Prolanis participants and may serve as an evidence based nonpharmacological intervention for community based elderly healthcare services.